Natural self‐emulsifying reversible hybrid‐hydrogel delivery (N'SERH) of tocopherol enhances bioavailability and modulates alcohol‐induced reproductive toxicity in rats. (8th December 2021) - Vismaya, K. U.; Noorjasmine, T. N.; Syam Das, S.; Kesavan, Lakshmi; Baby Chakrapani, P. S.; Krishnakumar, I. M.; Kumar, C. V. Sreeranjit
Abstract: Alpha‐tocopherol (α‐Toc), an antioxidant vitamin, has been widely prescribing in the treatment of infertility, in spite of its limited oral bioavailability. The present study describes the enhanced bioavailability and efficacy of a novel 'natural self‐emulsifying reversible hydrogel' (N'SERH)‐based oral delivery form of α‐Toc‐rich sunflower oil (Tα‐fen) using fenugreek galactomannan hydrogel scaffold (hybrid‐FENUMAT TM ). Tα‐fen was characterised by FTIR, SEM, TEM and DLS as a hybrid‐hydrogel powder. The bioavailability study on thirty ( n = 30) male Sprague Dawley rats randomised into two groups indicated 4.84‐fold increase in the oral bioavailability when the formulation was provided at 15 mg/kg b. wt. of α‐Toc by oral gavage. The efficacy study on 24 animals randomised into four groups as control, ethanol treated (4 mg/kg b. wt.), ethanol+unformulated, UTα (15 mg/kg b. wt.) and ethanol+formulation, Tα‐fen (15 mg/kg b. wt.) revealed significant improvement (* p < 0.05) and reversal of alcohol‐induced reproductive toxicity as evident from the enhanced sperm count, motility and viability parameters, testosterone levels, fructose content, and SDH activity and plasma antioxidant status among Tα‐fen‐treated rats, compared with unformulated, UTα‐treated group. Histopathology further confirmed the reversal of the alterations in the testes morphology of Tα‐fen‐treated animals, indicating its promising potential in the treatment of reproductive health issues.